Taḥlīlu al Akhṭā’i al Ṣautiyati ‘Inda Nuṭqi al Azāni wa Qirā’ati al Ṣalāti li al Ṭullābi fī Ma’hadi al Jazary Penyengat Rendah Telanai Pura Madīnati Jāmbī (Dirāsatun fī ‘Ilmi al Aṣwāti) - Amelia, Yuli Putri; Rosalinda, Rosalinda (Jurusan Bahasa dan Sastra Arab Fakultas Adab dan Humaniora UIN Sulthan Thaha Saifuddin Jambi, 2022)
Abstract:The learning a foreign language can not be separated from mistakes. Phonological errors are errors that occur in Arabic sounds, which include pronunciation errors, adding letters or replacing letters and others. This study aims to analyze phonological errors and the causes of errors as well as solutions to overcome errors in low stinging islamic boarding school al-jazari Telaipura Jambi city. The type of research used is qualitative research. The research data is obtained directly from the field or directly by collecting data when students announce or say the call to prayer and when reading the prayer readings and then identify errors in the reading. And this type of research is error analysis.From the error analysis conducted , there is a conclusion that phonological errors in pronouncing the adhan and reading the prayer in ma'had al - jazari low stinging telaipura are 1) the occurrence of errors including changing letters , adding letters or deleting letters and replacing harokat . 2 ) the cause of the error is the mother tongue or first language factor . Lack of understanding of the science of tajwid and makhorijul letters that are less precise as well as inadequate facilities and infrastructure. 3) The solution to the problems that occur is to continue to practice reading the Qur'an and pay attention to the reading of the students and the mental aqi of the readings that have been memorized by the students, emphasizing reading with the correct rules of tajwid and makhorijul letters. As well as providing adequate facilities such as books related to the rules of recitation.